Understanding Oceania Celebrating the University of the South Pacific and its collaboration with The Australian National University - Firth, Stewart; Naidu, Vijay (ANU Press, 2019)
"This book is inspired by the University of the South Pacific, the leading institution of higher education in the Pacific Islands region. Founded in 1968, USP has expanded the intellectual horizons of generations of students from its 12 member countries-Cook Islands, Fiji, Kiribati, Marshall Islands, Nauru, Niue, Samoa, Solomon Islands, Tokelau, Tonga, Tuvalu and Vanuatu-and been responsible for the formation of a regional elite of educated Pacific Islanders who can be found in key positions in government and commerce across the region. At the same time, this book celebrates the collaboration of USP with The Australian National University in research, doctoral training, teaching and joint activities. Twelve of our 19 contributors gained their doctorates at ANU, most of them before or after being students and/or teaching staff at USP, and the remaining five embody the cross-fertilisation in teaching, research and consultancy of the two institutions. The contributions to this collection, with a few exceptions, are republications of key articles on the Pacific Islands by scholars with extensive experience and knowledge of the region."